2019
DOI: 10.25100/cm.v50i2.4012
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity and self-rated health among older adults in Colombia

Abstract: Objective: To identify the relationship between religiosity and self-rated health among older adults in Colombia. Methods: Data are drawn from the SABE (Salud, Bienestar y Envejecimiento) Colombia Study, a cross-sectional survey conducted in 2015 involving 18,871 community-dwelling adults aged 60 years and older living in urban and rural areas of Colombia. Religiosity was assessed by self-rated religiosity (how religious are you: not at all, somewhat or very). Self-rated health during previous 30 days was asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 42 publications
(78 reference statements)
0
10
0
4
Order By: Relevance
“…Religious belief is also related to positive emotions, such as higher life satisfaction and happiness, which are the basis of good self‐perception (Reyes‐Ortiz et al., 2019). More religious people consider they are in better health than those who are less religious.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Religious belief is also related to positive emotions, such as higher life satisfaction and happiness, which are the basis of good self‐perception (Reyes‐Ortiz et al., 2019). More religious people consider they are in better health than those who are less religious.…”
Section: Resultsmentioning
confidence: 99%
“…More religious people consider they are in better health than those who are less religious. Furthermore, studies have shown that frequent religious attendance can promote healthier eating behaviors and reduce negative behaviors such as smoking and alcohol (Reyes‐Ortiz et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…They also have significantly lower mortality rates 9 - 11 . Religious people were also found to have better self-perceived health 12 , lower rates of functional impairment and disability 13 , and less prevalent health-related behaviors such as smoking, alcohol use, and drug abuse 14 , 15 . This is partially explained by the fact that religion imposes a set of rules not only associated with the ethical behavior of individuals but also with regard to food and drink intake, sexual activity, among other aspects, promoting healthy habits and lifestyles 3 , 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Asimismo, poseen tasas de mortalidad significativamente más reducidas 9 - 11 . También se ha observado que las personas religiosas tienen una mejor autopercepción de salud 12 , menores tasas de deterioro funcional y de discapacidad 13 , así como conductas relacionadas con la salud tales como tabaquismo, consumo de alcohol y abuso de drogas menos prevalentes 14 , 15 . Esto en parte se explica porque la religión impone una serie de reglas no solamente asociadas al comportamiento ético de los individuos, sino también en lo que respecta la ingesta de comidas y bebidas, la actividad sexual, entre otros aspectos, promoviendo hábitos y estilos de vida saludables 3 , 16 , 17 , lo que, en conjunto con el fortalecimiento de las redes de apoyo social y el sentido de certidumbre y estabilidad que permite afrontar de mejor manera los eventos estresantes que ocurren a lo largo de la vida 18 ,favorecen un mejor envejecer.…”
Section: Introductionunclassified
“…Studies involving SPH with the older population have used this measure to understand the factors related to healthy aging and well-being 1,3,5 . These studies have observed important associations between SPH and the presence of morbidities 7,8 , lifestyle, 8,9 and social participation 10,11 .…”
Section: Introductionmentioning
confidence: 99%